2012
DOI: 10.1073/pnas.1115133109
|View full text |Cite
|
Sign up to set email alerts
|

Learning predator promotes coexistence of prey species in host–parasitoid systems

Abstract: Ecological theory suggests that frequency-dependent predation, in which more common prey types are disproportionately favored, promotes the coexistence of competing prey species. However, many of the earlier empirical studies that investigated the effect of frequency-dependent predation were short-term and ignored predator-prey dynamics and system persistence. Therefore, we used long-term observation of population dynamics to test how frequency-dependent predation influences the dynamics and coexistence of com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(53 citation statements)
references
References 46 publications
3
50
0
Order By: Relevance
“…Biased parasitism rates on the common colour morph were consistent with changes in parasitism rates on the two colour morphs in the field (Langley et al, 2006). Similarly, learning resulted in frequency-dependent parasitism rates in Anisopteromalus calandrae (Howard) Hymenoptera: Pteromalidae) attacking two competing beetles Callosobruchus chinensis (L.) and Callosobruchus maculatus (Fabricius) (Coleoptera: Bruchidae) (Ishii & Shimada, 2012). Simulations and lab experiments demonstrated that learning, acting through frequency-dependent parasitism, increased the stability of the system, allowing for coexistence of the two beetle species (Ishii & Shimada, 2012).…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…Biased parasitism rates on the common colour morph were consistent with changes in parasitism rates on the two colour morphs in the field (Langley et al, 2006). Similarly, learning resulted in frequency-dependent parasitism rates in Anisopteromalus calandrae (Howard) Hymenoptera: Pteromalidae) attacking two competing beetles Callosobruchus chinensis (L.) and Callosobruchus maculatus (Fabricius) (Coleoptera: Bruchidae) (Ishii & Shimada, 2012). Simulations and lab experiments demonstrated that learning, acting through frequency-dependent parasitism, increased the stability of the system, allowing for coexistence of the two beetle species (Ishii & Shimada, 2012).…”
Section: Discussionsupporting
confidence: 50%
“…Similarly, learning resulted in frequency-dependent parasitism rates in Anisopteromalus calandrae (Howard) Hymenoptera: Pteromalidae) attacking two competing beetles Callosobruchus chinensis (L.) and Callosobruchus maculatus (Fabricius) (Coleoptera: Bruchidae) (Ishii & Shimada, 2012). Simulations and lab experiments demonstrated that learning, acting through frequency-dependent parasitism, increased the stability of the system, allowing for coexistence of the two beetle species (Ishii & Shimada, 2012). To our knowledge, the link between learning and frequency-dependent parasitism has not been demonstrated for facultative hyperparasitoids such as C. albifrons.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, work with some pteromalid wasps that utilize the same host species and developmental stages and have oviposition learning ability would be useful (e.g., A. calandrae; Shimada & Fujii, 1985;Ishii & Shimada, 2012;Sasakawa et al, 2013). This finding is notable because in parasitoid wasps that parasitize both larval and pupal hosts, the host's developmental stages have attracted little attention as factors affecting oviposition learning.…”
Section: Discussionmentioning
confidence: 99%
“…In oviposition learning, various non-host-associated cues can, in principle, serve as conditioned stimuli (e.g., artificial chemical odors; Takasu & Lewis, 2003;Collatz et al, 2006;Schurmann et al, 2012). In the real world, however, cues more-or-less associated with hosts, such as hostinduced plant volatiles in host herbivore-parasite systems (as discussed in Bleeker et al, 2006) and some of the odor components of the host per se (figure 1 in Ishii & Shimada, 2010; see also Ishii & Shimada, 2012), are considered to often serve as conditioned stimuli.…”
Section: Introductionmentioning
confidence: 99%
“…NFDS can operate either through enhanced survival or reproductive success of rare morphs. Our work, along with the work by Ishii & Shimada (), has elucidated a role of learning in generating NFD predation. In the study of NFD reproductive success, there is an analogous process: the ‘learned mate recognition’ hypothesis.…”
Section: Discussionmentioning
confidence: 99%